Penerapan Program Corporate Social Responsibility PT Djarum (Studi Kasus Kritik Eksploitasi Anak pada Audisi Umum Beasiswa Djarum) - Afrilia Ernes Natasya; Muhammad Sartono Bachtiar (Universitas Merdeka Malang, 2023)
Problems arise in PT Djarum's Sports Service Program when corporate identity is used in CSR programs. Criticism from a government agency highlighted the value of marketing the company's products with media program participants aged between 11 and 15 years. This qualitative research uses a study approach to understand the steps taken by the company. The informants involved were PT. Djarum and KPAI. Analysis of research data includes collecting, interpreting data, and drawing research results. The research results of the CSR program implemented by the Djarum Foundation have fulfilled the CSR principles namely sustainability, accountability, and openness, and criticism of the CSR program does not show child exploitation.Â Â Â